Plantar venous pump activity, Generalized Joint Hypermobility, and Foot Mobility in Ballerinas: A case-control study - TATAR, YAŞAR (My University, 2022)
Context: The plantar venous pump (PVP) is a vascular network located between the muscles of the foot arch. It has been suggested foot mobility is critical for PVP activation. Objective: This study investigates the effect of generalized joint hypermobility (GJH) on foot mobility and PVP activity in ballerinas and to determine how a short-term warm-up exercise impacts these parameters in the presence of GJH. Design: Prospective study. Methods: Twelve ballerinas (age = 16.73 [1.8] y) and 15 non-dancer-matched controls (age = 16.31 [2.1] y) were included. When performing weight-bearing activities, venous return parameters (diameter, velocity, and flow volume) from the posterior tibial vein were measured using color and spectral Doppler ultrasonography. Foot mobility was determined using navicular drop test. The participants performed a 10-minute cycling exercise to reveal its effect on reducing tissue stiffness. All measurements were performed synchronously and twice-before and after the cycling exercise. Results: The results showed the navicular height obtained before and after exercise in the ballerinas was significantly different compared with that obtained in the sitting position, and the values obtained in the 3 measurement positions in the nondancer group were significantly different from each other (P < .05). The difference between the venous diameter values measured before and after exercise and the reference value was significant in both groups (P < .001). There was a significant decrease in venous velocity following exercise in the nondancer group (P = .044). The venous volume values obtained after exercise were significantly different between the groups (P = .039). Conclusions: The GJH has no distinctive effect on foot mobility and PVP activity in ballerinas. The presence of GJH did not influence the effect of short-term warm-up exercise on foot mobility and PVP activity. We believe that measuring the navicular drop and venous return with a more precise synchronization may provide additional information regarding the link between arch tension and venous return.
Keywords: Tıp; Sağlık Bilimleri; Sosyal ve Beşeri Bilimler; Medicine; Health Sciences; Social Sciences and Humanities; Klinik Tıp (MED); Sosyal Bilimler (SOC); Klinik Tıp; Clinical Medicine (MED); Social Sciences (SOC); CLINICAL MEDICINE; female ballet dancer; venous diameter; venous flow volume; navicular drop; BALLET DANCERS; ANATOMY; LAXITY